Extensive Myelonecrosis: A Clinicopathological Study from A Tertiary Care Center - Jyothi, Neela Nirmala; Pamu, Pramod Kumar; Paul, T Roshini; Uppin, Shantveer G; Uppin, Megha S; Gundeti, Sadashivudu; Radhika, K (Annals of Pathology and Laboratory Medicine, 2020)
Background: The pathophysiology of bone marrow necrosis (BMN) remains unclear; however, the occlusion of microcirculation, accompanied by hypoxemia, causes damage to the cells and plays an important role in development of BMN. Methods: This is a descriptive study; a retrospective review of all trephine biopsies done over period of 22 months January 2017 to October 2018 in Department of pathology showing BMN were included. Only cases identified which showed extensive myelonecrosis > 20% of the diameter of trephine biopsy specimen was included in the study and BMN had to be diagnosed during life were included. Thirty cases met these criteria over this period. Result: In the study period, BMN was diagnosed in 30 samples among 3000 trephine biopsies showed extensive necrosis accounting for 1.0%. Almost all patients on peripheral blood examination shows anemia (100%), around 50% patients present with pancytopenia, followed by anemia with thrombocytopenia. From bone marrow aspiration and trephine biopsy examination shows 30 cases MN,among them 16 patients were acute leukemia either newly diagnosed or post chemotherapy follow-up cases, 10 out of 12 patients had severe bone pain before intuition of chemotherapy, acute leukemia followed by necrotizing granulomatous inflammation metastatic carcinoma were other causes for MN and one case was sickle cell hemolytic anemia. Conclusion: BMN is associated with many diseases, and yet presents with no clear patho physiology. In addition, clinical and laboratory characteristics are non-specific and, in many cases, symptoms are related to the causal condition that is most commonly a hematological disease.